Solar influences on atmospheric circulation - Georgieva, K.; Kirov, B.; Koucká Knížová, P. (Petra); Mošna, Z. (Zbyšek); Kouba, D. (Daniel); Asenovska, Y. (Journal of Atmospheric and Solar-Terrestrial Physics, 2012)
Various atmospheric parameters are in some periods positively and in others negatively correlated with solar activity. Solar activity is a result of the action of solar dynamo transforming solar poloidal field into toroidal field and back. The poloidal and toroidal fields are the two faces of solar magnetism, so they are not independent, but we demonstrate that their long-term variations are not identical, and the periods in which solar activity agents affecting the Earth are predominantly related to solar toroidal or poloidal fields are the periods in which the North Atlantic Oscillation is negatively or positively correlated with solar activity, respectively. We find further that solar poloidal field-related activity increases the NAM index, while solar toroidal field-related activity decreases it. This is a possible explanation of the changing correlation between the North Atlantic Oscillation and solar activity.